Homicide clearance in Western Europe - Liem, Marieke (European journal of criminology, 2019)
This study provides an overview of homicide clearance in four West European countries: Finland, the Netherlands, Sweden and Switzerland. Using data from the European Homicide Monitor, employing similar definitions and uniform coding schemes, this study allowed for unique cross-country comparisons in factors influencing differences in homicide clearance rates. Findings based on homicides occurring in the period 2009–14 revealed overall low homicide rates in all countries, with a wide variety in homicide clearance rates, ranging from 77 percent in the Netherlands to 98 percent in Finland. Results further showed that both event-based as well as victim-based characteristics significantly influenced the likelihood of homicide clearance, suggesting that homicide clearance rates can, for a large part, be attributed to the prevalent types of homicide in each of these European countries.